INFLUENCE OF SALINITY LEVELS ANALYSIS ON SETTLING VELOCITY OF FINE SEDIMENT GRAINS IN CILIWUNG ESTUARY: Salinity Levels on Settling Velocity of Fine Sediment Grains - Tri Wulan Sari; Denny Yatmadi; Rommy Martdianto; Sujito (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Transport of estuarine sediment have a highly complex method, which is the combined effects result of periodically reciprocating flow, ocean waves, and the electrochemical characteristic of sea water [1]. Settling velocity (SV) is such a parameter fundamental for sediment researchers so that its accurate resolution has been regarded as a top priority in correcting modelling numerical and conceptual understanding of fine sediment dynamics [2] [3]. The goal of this study is to analyze the effect of salinity levels on the settling velocity of fine sediment grains in the Ciliwung estuary, Jakarta. The method used is direct measurement using the hydrometer analysis method. The result of experiment shows salinity levels affect the settling velocity of fine sediment grains in the Ciliwung estuary. The higher salinity, more faster the settling velocity of fine sediment grains. The average settling velocity at distilled water salinity 0 ppt is 1.083 mm/minute, sea water with salinity 0.3 ppt is 1.537 mm/minute, and sea water with salinity of 0.6 ppt of 1.561 mm/minute.